2014
DOI: 10.1111/cup.12388
|View full text |Cite
|
Sign up to set email alerts
|

p40 is a more specific marker than p63 for cutaneous poorly differentiated squamous cell carcinoma

Abstract: For the diagnosis of cutaneous poorly differentiated SCC, p40 appears equally sensitive to MNF116 and p63. While labeling fewer cells, p40 labels without confounding staining of tumor cytoplasm or background cells. More importantly, p40 appears to be more specific for SCC than p63 and MNF116, each of which occasionally labels non-squamous tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 30 publications
1
17
0
2
Order By: Relevance
“…Another commonly used marker to establish epithelial lineage is p63, a member of the p53 gene superfamily . A recent study suggested that p40 appears equally sensitive and more specific for SCC compared with MNF116 and p63 . Our and others experience indicate that immunohistochemical markers for keratinocytes such as 34beta E12, p63, p40, MNF116 and AE1/3 should be performed in order to exclude poorly differentiated SCC with osteoclastic giant cell reaction in the lesions with osteoclastic giant cell reaction even without obvious keratinization.…”
Section: Discussionmentioning
confidence: 86%
“…Another commonly used marker to establish epithelial lineage is p63, a member of the p53 gene superfamily . A recent study suggested that p40 appears equally sensitive and more specific for SCC compared with MNF116 and p63 . Our and others experience indicate that immunohistochemical markers for keratinocytes such as 34beta E12, p63, p40, MNF116 and AE1/3 should be performed in order to exclude poorly differentiated SCC with osteoclastic giant cell reaction in the lesions with osteoclastic giant cell reaction even without obvious keratinization.…”
Section: Discussionmentioning
confidence: 86%
“…Metastatic anaplastic thyroid carcinoma with only a spindle cell component may require an initial immunohistochemical panel with S100, SOX‐10, pancytokeratin, CD68, CD10, p63 and desmin to exclude other spindle cell malignancies of the skin. The addition of PAX‐8 may aid in the diagnosis of cutaneous metastasis of anaplastic thyroid carcinoma, particularly if the tumor is composed exclusively of spindle cells …”
Section: Resultsmentioning
confidence: 99%
“…The absence of S100 and Melan‐A immunostaining, and the diffuse immunoreactivity for two smooth muscle markers (SMA and HHF‐35 muscle‐specific antigen), as well as the presence of focal calponin immunostaining, together with the expression of low‐molecular‐weight cytokeratins (such as CK8) excluded melanoma, atypical fibroxanthoma and pleomorphic dermal sarcoma, and favoured LMS; the latter was also supported by the histological features. The absence of p63, p40 and high‐molecular‐weight cytokeratins was critical to exclude squamous cell carcinoma …”
Section: Discussionmentioning
confidence: 99%